2019
DOI: 10.1371/journal.pone.0226336
|View full text |Cite
|
Sign up to set email alerts
|

Clonality testing in the lymph nodes from dogs with lymphadenomegaly due to Leishmania infantum infection

Abstract: IntroductionIn southern European countries, multicentric lymphoma and leishmaniosis are the main differential diagnoses in dogs presented with generalized lymphadenomegaly. The cytological examination is in some cases inconclusive and polymerase chain reaction (PCR) for antigen receptor rearrangement (PARR) has become a common method to confirm or rule out a lymphoproliferative neoplasia. According to the literature, leishmaniosis may lead to clonal arrangements and therefore to a false diagnosis of lymphoma, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…In our case series, clonality assessment was performed for all samples (results not showed), being all monoclonal, and in accordance with the previous IHC phenotype. No possible monoclonal peak with a polyclonal background due to L. infantum 58 was observed.…”
Section: Discussionmentioning
confidence: 89%
“…In our case series, clonality assessment was performed for all samples (results not showed), being all monoclonal, and in accordance with the previous IHC phenotype. No possible monoclonal peak with a polyclonal background due to L. infantum 58 was observed.…”
Section: Discussionmentioning
confidence: 89%
“…PCR for antigen receptor rearrangement (PARR) Test was performed commercially by Laboklin Polska sp.z o.o. according to the guidelines described in Reference 20.…”
Section: Methodsmentioning
confidence: 99%
“…The DNA product assessed by capillary electrophoresis can display a single length (monoclonal peak), thus corresponding to a monoclonal neoplastic proliferation, or display multiple lengths (polyclonal expansions), as expected in inflammatory conditions (Guillen et al 2021 ). Several primers are used for the complementary region 3 of T cell receptor and immunoglobulin heavy chain genes (e.g., Melendez-Lazo et al 2019 ; Waugh et al 2016 ). Recent studies have reported high sensitivity with figures over 80% for different types of lymphomas (Goto-Koshino et al 2015 ; Vessieres et al 2018 ; Waugh et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported high sensitivity with figures over 80% for different types of lymphomas (Goto-Koshino et al 2015 ; Vessieres et al 2018 ; Waugh et al 2016 ). Specificity is usually high but can be negatively affected by infectious diseases such as ehrlichiosis or leishmaniasis (Burnett et al 2003 ; Melendez-Lazo et al 2019 ). In the latter, 10% of animals may present monoclonal or biclonal patterns, leading to false diagnosis.…”
Section: Introductionmentioning
confidence: 99%